State financial assistance: essence, identification criteria, classification - N.G.; O.V. (Економіка, управління та адміністрування)
The article is devoted to the study of the essence, identification criteria and classification of state financial assistance. It was noted that the variety of forms, types, and directions of provision of grant funds determines the need to clarify the theoretical foundations of providing state financial support to economic entities, which actualizes the topic of scientific research. The purpose of the article is to define the concept of "state financial assistance" based on the evaluation of scientific approaches to its interpretation, the selection of criteria for its identification and the clarification of the classification features of its division for further research into the directions of appointment and provision. The study of scientific literature on the directions of providing assistance to enterprises made it possible to identify «theoretical gaps» in its interpretation, caused by different perceptions of its content. Based on the terminological analysis of the differences between the concepts of «grant», «state financial support», «state financial assistance», the following was determined: the concept of «state financial support» is a broader concept than «state financial assistance» in terms of content, since the latter should meet a number of criteria defined for state measures that characterize its essence. The article highlights the criteria of a state measure that identifies it as state financial assistance: 1) availability of state resources; 2) the presence of an economic benefit (competitive advantage) that arises when the economic entity is transferred state resources; 3) selectivity (selectivity) of assistance for the implementation of the measure; 4) distortion of competition due to the provision of such state aid; 5) the need for state financial control. Regarding the relationship between the concepts of «grant» or «grant financial assistance» and «state financial assistance», it was concluded that a grant is a set of financial and other resources provided on the basis of free, non-refundable, targeted financing at the expense of various sources (funds from state, local budgets, international technical assistance) for the purpose of implementing a specific event or investment project. At the same time, the concept of state financial assistance is broader, as it includes various types, including grant support. The authors clarified the classification of types of state financial assistance according to various characteristics, which will contribute to the expansion of the directions of its appointment and provision, especially in the conditions of wartime and post-war reconstruction.